Clinical and ex vivo laboratory comparison of the self‐sealing properties and dimensional stability between the femtosecond laser and manual clear corneal incisions. Issue 4 (30th November 2017) - Kojima, Takashi; Takagi, Mari; Ichikawa, Kei; Horai, Rie; Sakai, Yukihiro; Tanaka, Yoshiki; Tamaoki, Akeno; Ichikawa, Kazuo
Abstract: Purpose: To compare the self‐sealing features and dimensional stability between the femtosecond laser (FL) and manual knife corneal incision. Methods: For the clinical study, 29 consecutive eyes from 29 patients and 28 eyes from 28 patients who underwent cataract surgery with FL corneal incision and manual knife incision, respectively, were enrolled. Immediately after cataract surgery, the self‐sealing features of the corneal incisions were evaluated. Scanning electron microscopy (SEM) images were obtained. For the experimental study, clear corneal incisions with a knife or FL with different energy settings (3, 6 and 9  μ J) were created in fresh porcine eyes, followed by a stress test. The incision width was measured before and after the stress test. Results: In the clinical study, the knife group had a higher self‐sealing score (0.60 ± 0.49 points) than the FL group (0.17 ± 0.38 points). In the experimental study, the deformation rate in the knife incision (5.04 ± 1.93) was significantly lower than that in the FL with any energy. The deformation rate in the 9  μ J (12.98 ± 2.76) was significantly higher than in the 3  μ J (8.54 ± 2.38) and 6  μ J (8.82 ± 2.85) FL energies. Scanning electron microscopy (SEM) images revealed that the corneal stromal surface of the knife incision was smoother than that of the FL. Higher energy FL showed more irregular surfaces. Conclusion: Higher FL energy tended to widen a clear corneal incision when mechanical stress was applied. The histological differences at the inner tunnel surface may cause differences in wound stability of the corneal incision.